Weerspiegeld in een waterglas Maurice Gilliams, 1900-1982 - Portegies, Annette 1968- (Athenaeum-Polak & Van Gennep, 2022)
Biografie van de Vlaamse auteur (1900-1982)
Keywords: Gilliams, Maurice -- 1900-1982; Gilliams, Maurice; Biografieën; Biografie